IMPLEMENTASI NILAI-NILAI BUDAYA ORGANISASI MELALUI SOSIALISASI BUDAYA ORGANISASI - Dwi Irawati (SEGMEN Jurnal Manajemen dan Bisnis, 2009)
This article describes the significant impacts of promoting corporate culture foremployees, especially new recruits, in their understanding of corporate culture orcorporate values. Promoting corporate culture and/or corporate values is often used bymany organizations to help its employee recognize the organization’s condition andsurroundings. The success of this process depends on the role of the manager as well asthe employees’s involvement in achieving “person-culture fit”, degrees of efficacy inreaching according to organizational culture, and accuracy of selected socializationmethod and weared.Keywords: organization, corporate culture, person-culture fir, corporate value,socialization